2010
DOI: 10.3109/14767050903511560
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of free vascular endothelial growth factor in the maternal and foetal circulations during pregnancy: A cross-sectional study

Abstract: Circulating VEGF is usually bound to the soluble form of its receptor 1 (sFlt-1). High levels of sFlt-1 are secreted by the syncytiotrophoblast during pregnancy, and so free plasma VEGF is undetectable in the maternal circulation. In contrast, our findings are the first to show free plasma VEGF in the umbilical circulation. We speculate that this free VEGF may promote angiogenesis in the foetus and placenta. Our data imply that sFlt-1 is not present in the cord blood, and that secretion by the syncytiotrophobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The polarized secretion of sFlt-1 into the maternal compartment but not into the fetal side enables angiogenesis, which is essential for normal development to take place in the materno-fetal unit and is thought to protect the mother against excessive angiogenic stimulation. 53 In this study, maternal MDA levels showed an association with sFlt-1, which by itself has been shown to induce oxidative stress. A recent study in rats has shown that the chronic infusion of plasma sFlt-1 causes hypertension associated with increased oxidative stress and endothelial dysfunction, although the mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The polarized secretion of sFlt-1 into the maternal compartment but not into the fetal side enables angiogenesis, which is essential for normal development to take place in the materno-fetal unit and is thought to protect the mother against excessive angiogenic stimulation. 53 In this study, maternal MDA levels showed an association with sFlt-1, which by itself has been shown to induce oxidative stress. A recent study in rats has shown that the chronic infusion of plasma sFlt-1 causes hypertension associated with increased oxidative stress and endothelial dysfunction, although the mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 81%
“…As there is no increased demand for angiogenesis in the mother peripherally, maternal levels are low. 52,53 Slightly reduced VEGF levels in plasma may also be partly due to the complex with circulating sFlt-1 that is released from the placenta. The polarized secretion of sFlt-1 into the maternal compartment but not into the fetal side enables angiogenesis, which is essential for normal development to take place in the materno-fetal unit and is thought to protect the mother against excessive angiogenic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Cord sFlt-1 levels were lower as compared to maternal levels at every time point during gestation. It has been reported that there is a polarized secretion of sFlt-1 into the maternal but not in the fetal compartment for angiogenesis [41].…”
Section: Discussionmentioning
confidence: 99%
“…These 2 conditions combine in the hypertensive pregnancy, the most severe form of which is preeclampsia, which also implicates growth factor dysregulation. 626,3234 Data on angiogenin and VEGF in preeclampsia are conflicting. For example, Reuvekamp et al 14 reported low VEGF but no difference in angiogenin in 30 women with preeclampsia (mean 524 ng/mL) compared with 30 NonPCs (mean 670 ng/mL), although P = .058 implies a type 1 (false negative due to small number) artifact.…”
Section: Discussionmentioning
confidence: 99%